2023
DOI: 10.1111/eci.14108
|View full text |Cite
|
Sign up to set email alerts
|

The association of testosterone with sarcopenia and frailty in chronic liver disease

Lampros Chrysavgis,
Magdalini Adamantou,
Anna Angelousi
et al.

Abstract: BackgroundTestosterone is an important anabolic hormone responsible for maintaining body composition and muscle mass and circulates mostly albumin‐bound, or sex hormone binding globulin (SHBG)‐bound or free in the plasma. Of these fractions, the latter is bioactive and exerts the androgenic effects on male population. Liver cirrhosis, the advanced stage of any chronic liver disease characterized by permanent distortions to the hepatic architecture, disrupts the hypothalamic‐pituitary‐gonadal axis, leading to d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 139 publications
0
2
0
Order By: Relevance
“…Age-related testosterone decline is associated with the development of sarcopenia ( 32 , 33 ) and, testosterone replacement therapy has been reported to increase muscle strength and lean body mass ( 34 , 35 ). In addition, randomized controlled trials in patients with liver cirrhosis have demonstrated the benefit of testosterone administration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…Age-related testosterone decline is associated with the development of sarcopenia ( 32 , 33 ) and, testosterone replacement therapy has been reported to increase muscle strength and lean body mass ( 34 , 35 ). In addition, randomized controlled trials in patients with liver cirrhosis have demonstrated the benefit of testosterone administration ( 36 ).…”
Section: Discussionmentioning
confidence: 99%
“…That effect could be mitigated by advising MASLD patients to increase their physical exercise in the form of both aerobic exercise and resistance training in order to minimize the potential harmful effect on skeletal muscle strength and the development of frailty, which is a rapidly recognized feature in patients with MASLD [116,117]. In this setting, specific pharmacological agents for preserving lean muscle mass have been proposed by the literature, and they include urocortin 2 and urocortin 3, testosterone, growth hormone, and activin type II receptor inhibitors [118,119]. Furthermore, MASLD as a multisystemic disease is strongly related to cardiovascular events, while the MASH fibrosis stage is an independent predictor of incident cardiovascular disease [120].…”
Section: Closing Remarks and Future Perspectivesmentioning
confidence: 99%
“…Besides aging, factors like obesity, dyslipidemia, metabolic syndrome, hypertension, diabetes mellitus, and chronic kidney disease have been linked to decreased TT levels and an elevated risk of developing TD [ 3 6 ]. TD can result in muscle atrophy, reduced strength, compromised cognitive function, poorer sleep quality, an increased risk of depression, and reduced life satisfaction in men [ 7 , 8 ]. Understanding the factors leading to this decline is essential for preventing TD and developing new treatments.…”
Section: Introductionmentioning
confidence: 99%